2016
DOI: 10.2519/jospt.2016.6577
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Chondrolabral Pathology Have Bilateral Functional Impairments 12 to 24 Months After Unilateral Hip Arthroscopy: A Cross-sectional Study

Abstract: T t STUDY DESIGN:Cross-sectional study. T t BACKGROUND:Functional task performance in patients with chondrolabral pathology following hip arthroscopy is unknown. T t OBJECTIVES:To investigate in people with chondrolabral pathology following hip arthroscopy (1) the bilateral differences in functional task performance compared to controls, (2) the association of hip muscle strength with functional task performance, and (3) the association of functional task performance scores with good outcome, as measured by In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Changes in neuromuscular function of the hip are associated with intra‐articular hip joint pathology. Recent systematic reviews (Diamond et al, ; Freke et al, ; Mayne et al, ) and research studies have examined physical impairments associated with FAI syndrome, acetabular labral pathology and chondropathology, and have found impaired hip range of motion (Kemp et al, ; Diamond et al, ), reduced hip muscle strength (Casartelli et al, ; Harris‐Hayes et al, ; Mendis et al, ; Kemp et al, ; Nepple et al, ; Diamond et al, ), impaired functional task performance (Hatton et al, ; Bagwell et al, ; Charlton et al, ; Kemp et al, ; Samaan et al, ), and altered gait biomechanics (Kennedy et al, ; Brisson et al, ; Hunt et al, ; Ng et al, ). With respect to hip muscle size, previous research has investigated size of the gluteal muscles in patients with chronic hip joint pain (Mastenbrook et al, ) and of the individual hip flexor muscles in patients with acetabular labral pathology (Mendis et al, ); however, no research to date has investigated the individual hip abductor, hip extensor, or hip external rotator muscles in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in neuromuscular function of the hip are associated with intra‐articular hip joint pathology. Recent systematic reviews (Diamond et al, ; Freke et al, ; Mayne et al, ) and research studies have examined physical impairments associated with FAI syndrome, acetabular labral pathology and chondropathology, and have found impaired hip range of motion (Kemp et al, ; Diamond et al, ), reduced hip muscle strength (Casartelli et al, ; Harris‐Hayes et al, ; Mendis et al, ; Kemp et al, ; Nepple et al, ; Diamond et al, ), impaired functional task performance (Hatton et al, ; Bagwell et al, ; Charlton et al, ; Kemp et al, ; Samaan et al, ), and altered gait biomechanics (Kennedy et al, ; Brisson et al, ; Hunt et al, ; Ng et al, ). With respect to hip muscle size, previous research has investigated size of the gluteal muscles in patients with chronic hip joint pain (Mastenbrook et al, ) and of the individual hip flexor muscles in patients with acetabular labral pathology (Mendis et al, ); however, no research to date has investigated the individual hip abductor, hip extensor, or hip external rotator muscles in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, there are currently only a small number of studies reporting on PBMs in patients after FAIS surgery. 7,17,43 More than 2 years after HA, participants in a study by Tijssen et al 43 performed within 90% of the limb symmetry index during tests of single-leg balance, single-leg squat control, and single-leg hop. Two further studies compared patients 1 to 2 years after HA with a control group and reported decreased single-leg squat control as well as reduced hop and single-leg bridge performance.…”
mentioning
confidence: 99%
“…The most important secondary outcomes are presented as key secondary outcomes. The key secondary outcomes are the other subscales of the HAGOS covering Symptoms, Physical function in daily living, Physical function in Sport and Recreation and Quality of Life; Single leg hop for distance;29 30 adverse and serious adverse events (see box 1). 31 Usage of painkillers (yes/no) and type of analgesics is also part of the key secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%